Disinfection of gloved hands for multiple activities with indicated glove use on the same patient. Issue 1 (September 2017) - Kampf, G.; Lemmen, S.
Summary: Most hand hygiene guidelines recommend that gloves should be changed during patient care when an indication for hand disinfection occurs. Observational studies indicate that the majority of healthcare workers (HCWs) do not disinfect their hands at all during continued glove wear. The aim of this narrative review is to assess the potential benefits and risks for disinfecting gloved hands during patient care for multiple activities with indicated glove use on the same patient. Continued glove wear for multiple activities on the same patient often results in performing procedures, including aseptic procedures with contaminated gloves, especially in a setting where there are many indications in a short time, e.g. anaesthetics or accident and emergency departments. Of further note is that hand hygiene compliance is often lower when gloves are worn. To date, three independent studies have shown that decontamination is at least as effective on gloved hands as on bare hands and that puncture rates are usually not higher after up to 10 disinfections. One study on a neonatal intensive care unit showed that promotion of disinfecting gloved hands during care on the same patient resulted in a significant reduction in the incidence of late-onset infections and of necrotizing enterocolitis. We conclude that disinfection of gloved hands by HCWs may substantially reduce the risk of transmission when gloves are indicated for the entire episode of patient care and when performed during multiple activities on the same patient.